2012
DOI: 10.1029/2012gl051002
|View full text |Cite
|
Sign up to set email alerts
|

Summer thermal structure and anticyclonic circulation of Lake Erie

Abstract: [1] In most thermally stratified lakes, the summer thermocline has the shape of a "dome", with a shallower depth offshore than nearshore. This configuration is accompanied by a lake-wide cyclonic circulation. Lake-wide observations of subsurface temperature in central Lake Erie revealed an atypical "depressed" or "bowl-shaped" thermocline in late summer, with a deeper thermocline in the middle of the lake and a shallower thermocline nearshore. Currents measured in the central basin when the bowl-shaped thermoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 45 publications
4
46
0
Order By: Relevance
“…Similar anticyclonic currents form in Lake Erie in summer months (Beletsky et al, 2012) and the high concentrations of plastic in Lake Erie's eastern basin have been attributed to this feature (Eriksen et al, 2013;Driedger et al, 2015). Yet, our plastic transport model did not predict a permanent plastic "garbage patch" in Lake Erie (Figures 9, 10A).…”
Section: Lake Erie Plastic Transport Modelmentioning
confidence: 86%
See 1 more Smart Citation
“…Similar anticyclonic currents form in Lake Erie in summer months (Beletsky et al, 2012) and the high concentrations of plastic in Lake Erie's eastern basin have been attributed to this feature (Eriksen et al, 2013;Driedger et al, 2015). Yet, our plastic transport model did not predict a permanent plastic "garbage patch" in Lake Erie (Figures 9, 10A).…”
Section: Lake Erie Plastic Transport Modelmentioning
confidence: 86%
“…This was especially pronounced along both the northern and southern coasts in June, the month the majority of our field survey took place. Later in the season, the large-scale anticyclonic circulation that typically develops in mid and late summer (Beletsky et al, 2012) influenced the movement of plastics. Due to that circulation feature, particles released along the southern coast east of Cleveland were often transported westward (Figure 9).…”
Section: Lake Erie Plastic Transport Modelmentioning
confidence: 99%
“…Physical modeling efforts have revealed that lowamplitude, high-frequency inertial waves (Poincaré waves with a dominant period of 17.3 h) are a prominent feature of the variability in Lake Erie's thermocline (Bouffard et al 2012). In addition, large-scale anticyclonic circulation patterns generate a bowl-shaped thermocline in Lake Erie's central basin, which results in varying degrees of upward forcing of the thermocline near the edges of the basin (Beletsky et al 2012). Thus, instability of the thermocline and fluctuations in the thickness of the hypolimnion can function to increase heterogeneity in the hypoxic zone, especially in regions where the thermocline contacts the sediment.…”
Section: Discussionmentioning
confidence: 97%
“…Under these conditions, surface seiches, which are unaffected by rotation are preferentially excited. Further analysis is required to examine the impact of Poincar e waves on other hydrodynamic processes such as residual and mean-annual circulation patterns (e.g., Schwab and Bennett 1987;Beletsky et al 1999Beletsky et al , 2012Stocker and Imberger 2003).…”
Section: Horizontal Modal Structurementioning
confidence: 99%